Oncogenic circular RNA circ_0007534 contributes to paclitaxel resistance in endometrial cancer by sponging miR-625 and promoting ZEB2 expression - Yi, Hanjie; Han, Yongqing; Li, Shanfeng (Frontiers in Oncology, 2022)
Circular RNAs (circRNAs) and epithelial to mesenchymal transition (EMT) have been implicated in the development of human cancer and paclitaxel resistance. CircRNA circ_0007534 has been described as a key oncogenic circular RNA that is upregulated in a variety of cancer tissues. However, whether circ_0007534 causes EMT and paclitaxel resistance in endometrial cancer is still unknown. In this work, we revealed that circ_0007534 levels were significantly higher in endometrial cancer tissues, and that high circ_0007534 expression was associated with poor differentiation, advanced tumor stage, cancer invasion, cancer metastasis, and poor prognosis in endometrial cancer patients. Overexpression of circ_0007534 boosted endometrial cancer cell proliferation, invasion, EMT, and paclitaxel resistance. Knockdown of circ_0007534 restored paclitaxel sensitivity and reversed EMT in endometrial cancer cells. We also showed that circ_0007534 enhanced endometrial cancer aggressiveness, progression, and paclitaxel resistance by sponging microRNA-625 (miR-625) and subsequently increasing the expression of the miR-625 target gene ZEB2. Our cell functional studies demonstrated that inhibiting miR-625 or increasing ZEB2 mimicked the effects of circ_0007534 overexpression. Consequently, our data show that circ_0007534 plays a crucial role in EMT and paclitaxel resistance through miR-625/ZEB2 signaling. Targeting the circ_0007534/miR-625/ZEB2 pathway might be an effective strategy for overcoming paclitaxel resistance in endometrial cancer.